Uso de tubos de Venturi na aeração de um reator de leito móvel aplicado na remoção de matéria orgânica e nitrogênio - Nonaka, Fernanda Martins (2019)
The main objective of this work was to evaluate the effect of use of the Venturi tubes on the aeration a mobile bed reactor with immobilized biomass and semi-continuous flow, operating under intermittent aeration, to remove nitrogen and carbon from an effluent from a University Restaurant. The reactor was built in a polyethylene water tank with a capacity of 500L. The support medium used to fix the microorganisms was Biobobs® arranged in a mobile form and occupying about 12% of the reactor. The periods of aeration and non-aeration were 3 hours and 1 hour, respectively. As a result, it was adopted the use of 3 Venturis tubes in the System, which presented KLa of 16,31 h-1, oxygen transfer rate of 62,86 gO2h-1, power consumption of 0,048 kW and Oxygen Efficiency of 1,319 kgO2kWh-1. It was also observed that the best operational condition was with HRT of 1.67 d, which showed a TN removal efficiency of 72% and a COD removal of 97%. On the other hand, when the system was operated with HRT of 2.5d and 5d, it presented lower TN removal efficiencies, in the values of 43% and 54%, respectively. Regarding the removal of COD, the efficiencies with HRT of 2.5d and 5d were 77% and 84% respectively, indicating an effective carbon removal even with higher HRT. There was no significant presence of biomass in the effluent, indicating that the biomass remained immobilized to the support medium.